Atomic force microscopy and Raman scattering spectroscopy studies on heat-induced fibrous aggregates of β-lactoglobulin. Issue 2 (2003) - Ikeda Ikeda, Shinya Shinya
Abstract : Nanometer-thick fibrous aggregates of β -lactoglobulin alone and its mixture with other globular proteins were formed by heating aqueous solutions at pH 2 with maintaining an effective level of electrostatic repulsion among denatured protein molecules. In atomic force microscopy (AFM) images, these fibrous aggregates appeared to be fairly uniform in width and height and composed of strings of globular elements. Fibrous aggregates formed in β -lactoglobulin individual systems were only slightly thicker than the size of the native β -lactoglobulin monomer, while those formed in the presence of other globular proteins were more than twice thicker, suggesting that different species of globular proteins were incorporated into each individual fibrous aggregate in the mixed systems. At neutral pH, aggregates were generally composed of ellipsoidal primary particles much larger than the size of the monomer, suggesting that aggregation proceeds in two steps at neutral pH. Molecular structural changes probed by Raman scattering spectroscopy revealed that considerable fractions of β -sheet structures remained to be folded during the formation of fibrous aggregates but α -helix structures were partially lost. It was also suggested that a limited extent of hydrophobic interactions among heat-denatured protein molecules is required for the fibrous aggregation.